3D cell sheet structure augments mesenchymal stem cell cytokine production - Sophia Bou-Ghannam (Nature Portfolio, 2021)
Abstract Mesenchymal stem cells (MSCs) secrete paracrine factors that play crucial roles during tissue regeneration. An increasing body of evidence suggests that this paracrine function is enhanced by MSC cultivation in three-dimensional (3D) tissue-like microenvironments. Toward this end, this study explored scaffold-free cell sheet technology as a new 3D platform. MSCs cultivated on temperature-responsive culture dishes to a confluent 2D monolayer were harvested by temperature reduction from 37 to 20 °C that induces a surface wettability transition from hydrophobic to hydrophilic. Release of culture-adherent tension induced spontaneous cell sheet contraction, reducing the diameter 2.4-fold, and increasing the thickness 8.0-fold to render a 3D tissue-like construct with a 36% increase in tissue volume. This 2D-to-3D transition reorganized MSC actin cytoskeleton from aligned to multidirectional, corresponding to a cell morphological change from elongated in 2D monolayers to rounded in 3D cell sheets. 3D culture increased MSC gene expression of cell interaction proteins, β-catenin, integrin β1, and connexin 43, and of pro-tissue regenerative cytokines, vascular endothelial growth factor (VEGF), hepatocyte growth factor (HGF), and interleukin-10 (IL-10), and increased VEGF secretion per MSC 2.1-fold relative to 2D cultures. Together, these findings demonstrate that MSC therapeutic potency can be enhanced by 3D cell sheet tissue structure.